The relationship of menstrual preparation on menarche, emotional response to menstruation, and sources of menstrual information. - Salde, Ma. Weena S
The occurrence of first menstruation is a big event in an adolescent girl's life. This research would like to know if there is a relationship between menstrual preparation on menarche and current emotional response to menstruation. This also aimed to solicit direct recommendations from adolescent girl's on how to prepare other girls for menstruation. Some parts of the research questionnaire used in he data gathering were adopted from the research study of Rierdan and Koff (1995) published in the Adolescence Magazine (Winter 1995). Sixty-six (66) of the third year female high school students of Pontevedra National High School in Pontevedra (PNHS) , Negros Occidental participated in the study. The sample was randomly chosen as respondents. Results of the study showed that no relationship exists between emotional response to menstruation and menstrual preparation on menarche. Likewise, no relationship exists between emotional response to menstruation and sources of menstrual preparation except for the degree of helpfulness of health providers. Findings also showed that adolescent girls perceived their mothers as very helpful in preparing them for menstruation.